Measurements and modelling of fast-ion redistribution due to resonant MHD instabilities in MAST. (3rd November 2015) - Jones, O M; Cecconello, M; McClements, K G; Klimek, I; Akers, R J; Boeglin, W U; Keeling, D L; Meakins, A J; Perez, R V; Sharapov, S E; Turnyanskiy, M
Abstract: The results of a comprehensive investigation into the effects of toroidicity-induced Alfvén eigenmodes (TAE) and energetic particle modes on the NBI-generated fast-ion population in MAST plasmas are reported. Fast-ion redistribution due to frequency-chirping TAE in the range 50 kHz–100 kHz and frequency-chirping energetic particle modes known as fishbones in the range 20 kHz–50 kHz, is observed. TAE and fishbones are also observed to cause losses of fast ions from the plasma. The spatial and temporal evolution of the fast-ion distribution is determined using a fission chamber, a radially-scanning collimated neutron flux monitor, a fast-ion deuterium alpha spectrometer and a charged fusion product detector. Modelling using the global transport analysis code Transp, with ad hoc anomalous diffusion and fishbone loss models introduced, reproduces the coarsest features of the affected fast-ion distribution in the presence of energetic particle-driven modes. The spectrally and spatially resolved measurements show, however, that these models do not fully capture the effects of chirping modes on the fast-ion distribution.